Remaining effect of long-term soil tillage on plant biomass yield and water erosion in a Cambisol after transition to no-tillage - Wolschick, Neuro Hilton; Bertol, Ildegardis; Barbosa, Fabrício Tondello; Bagio, Bárbara; Biasiolo, Luiz Antonio (Soil & tillage research, 2021)
•Soil disturbance due to previous tillage history affects the efficiency of no-tillage.•Long-term no-tillage results in higher phytomass yield and less erosion and runoff.•Change of tillage to no-tillage reduced soil losses in the first year.•Change of tillage to no-tillage did not reduce runoff in initial 3-year period. No-tillage combined with soil cover by plant residues is important strategy to reduce soil erosion caused by cultivation methods that involve soil tillage. However, the impact that history of soil disturbance caused by tillage has on plant production and water erosion after the establishment of no-tillage requires a detailed assessment. This research aimed to evaluate the residual effect of soil managed for 23 years with different intensities of mechanical preparation on vegetable biomass yield and soil and water losses by erosion after transition to no-tillage, in a Cambisol in southern Brazil. For three years (2015–2018), the following treatments were evaluated: NT1) long-term no-tillage, conducted for 23 years (control); NT2) no-tillage established after 23 years of cultivation under alternation of different tillage; NT3) no-tillage established after 23 years of cultivation under minimum tillage (scarification with chisel plough followed by harrowing); NT4) no-tillage established after 23 years of cultivation under conventional tillage (plowing with disc plough followed by two harrowings); and NT5) no-tillage established after 23 years of soil kept uncovered and without cultivation (bare soil). During this research, in all treatments, a cover crop mixture was grown in the winter and maize in the summer. Rainfall characteristics, water erosion and dry vegetable biomass (DVB) of the crops were evaluated in plots of 3.5 × 22.1 m, with an average slope of 0.102 m m−1. The history of long-term soil tillage influenced plant biomass yield and affected the effectiveness of no-tillage in reducing soil erosion and runoff after its establishment. NT1 had a large accumulated DVB, significantly (p < 0.05) higher than NT2, NT4 and NT5 in the cover crop mixture cultivation and higher than NT5 in the maize cultivation. Accumulated soil losses by erosion followed the order (p < 0.05): NT5 = NT4> NT3 = NT2 > NT1. Water losses by runoff were greater in NT3, NT4 and NT5 and lowest value occurred in NT1 (p < 0.05). In general, DVB reflected the previous management, so that NT4 and NT5 presented lower yields. There was a decrease in soil losses due to erosion over time in the treatments, on the other hand, water losses did not have the same tendency, being little influenced by the change in management and reflected the degree of soil disturbance by the previous history of soil tillage.